Dihydrotestosterone binding by cultured human fibroblasts. Comparison of cells from control subjects and from patients with hereditary male pseudohermaphroditism due to androgen resistance. - Griffin, J E (1976)
Dihydrotestosterone binding was measured in culture fibroblasts from 14 control subjects and from 12 patients with five different types of hereditary male pseudohermaphroditism. Two assays of binding were used--an intact monolayer assay and density gradient centrifugation of cell extracts. In the intact monolayer assay of normal cells the uptake of [3H]dihydrotestosterone consisted of two components. The first was a high affinity component that exhibited saturation at approximately 1 nM dihydrotestosterone. The second was a low affinity component that was not saturable with concentrations of steroid up to 5 nM. Twice the number of high affinity binding sites were present in fibroblasts grown from genital skin (foreskin, labia majora, and scrotum) as from nongenital sites (37 vs. 14 fmol/mg protein). In the density gradient assay in 5-10% sucrose, the major peak of dihydrotestosterone binding was in the 8S region in low molarity buffer and in the 4S region in 0.5 M KCl. High affinity binding was normal in cells from two patients with familial incomplete male pseudohermaphroditism, type 2, an autosomal recessive defect in which dihydrotestosterone formation is deficient, and in cells from a patient with male pseudohermaphroditism due to 17 beta-hydroxysteroid dehydrogenase deficiency, an autosomal recessive defect of testosterone synthesis. High affinity binding was low by both methods in fibroblasts from five patients with complete testicular feminization. Furthermore, binding by both methods was also low in cells from three subjects with familial incomplete male pseudohermaphroditism, type 1, a presumed X-linked recessive disorder of androgen resistance, and in fibroblasts grown from a subject with the incomplete form of testicular feminization. The finding that dihydrotestosterone binding is abnormal in two forms of hereditary androgen resistance in addition to complete testicular feminization suggests either that these disorders are the result of allelic mutations affecting the function of the androgen-binding protein or that normal dihydrotestosterone binding requires the participation of more than one gene product.